1981
DOI: 10.3102/00028312018002207
|View full text |Cite
|
Sign up to set email alerts
|

Election of High School Mathematics by Females and Males: Attributions and Attitudes

Abstract: Males, more than females, elect advanced mathematics courses. This differential in the number of mathematics courses elected has been cited as a major explanation of sex-related differences in adults' mathematics performance and in their participation in mathematics-related careers. Knowledge about some of the variables that enter into the decision to persist in the study of mathematics is essential for those who are interested in encouraging females, as well as males, to adequately prepare themselves in mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(12 citation statements)
references
References 9 publications
(7 reference statements)
2
9
0
Order By: Relevance
“…Confirming earlier research (Eccles et al, 1985;Gavin, 1997;Gjertsen, 1999;Kelly, 1986;Leder, 1988;Pedro, Wolleat, Fennema, & Becker, 1981;Tocci & Engelhard 1991), all of these talented young women understood that math was useful in life; this view was fostered in both home and school environments. Making learning meaningful and useful to these young women appeared to have an impact on mathematics achievement.…”
Section: Parental Teachingsupporting
confidence: 78%
“…Confirming earlier research (Eccles et al, 1985;Gavin, 1997;Gjertsen, 1999;Kelly, 1986;Leder, 1988;Pedro, Wolleat, Fennema, & Becker, 1981;Tocci & Engelhard 1991), all of these talented young women understood that math was useful in life; this view was fostered in both home and school environments. Making learning meaningful and useful to these young women appeared to have an impact on mathematics achievement.…”
Section: Parental Teachingsupporting
confidence: 78%
“…A similar result was reported in various studies in which mathematics anxiety levels of girls were higher than boys" (Varol, 1990;Girgin, 1990;Dong, 1994). Research also emphasized that in society mathematics anxiety was experienced more often by females than by males (Betz, 1978;Dutton, 1956;Pedro, Wolleat, Fennema, & Becker, 1981;Tobias & Weissbrod, 1980). Another result of this study showed that whether students had prior special tutoring did not create a difference in their mathematics anxiety scores.…”
Section: Discussionsupporting
confidence: 88%
“…In 1980, only 39 percent of black and Hispanic high school seniors had persisted in mathematics as far as geometry, compared with 60 percent of white seniors and 79 percent of the Asian seniors (Malcolm, 1985). Several researchers have proposed that high school mathematics enrollment serves as a "critical filter" for careers in the sciences, and that the underrepresentation of females and minorities can be traced to that factor (Fennema, 1977;Fennema & Sherman, 1977;Pedro, Wolleatt, Fennema & Becker, 1981). There have been studies, however, that have challenged the idea of differences in enrollments being a primary factor with regard to females.…”
Section: Interest and Enrollmentsmentioning
confidence: 99%